Librarians’ and teachers’ conceptions of multiliteracies in the context of Finnish curriculum reform - Siinamari Ylivuori; Anu Ojaranta (Information Research: An International Electronic Journal, 2023)
Introduction. The aim of this study is to describe how the concept of multiliteracies is interpreted by teachers and librarians.